Optimization of Soil Washing to Reduce the Selenium Levels of Seleniferous Soil from Punjab, Northwestern India. Issue 6 (1st November 2018) - Wadgaonkar, Shrutika L.; Ferraro, Alberto; Race, Marco; Nancharaiah, Yarlagadda V.; Dhillon, Karaj S.; Fabbricino, Massimiliano; Esposito, Giovanni; Lens, Piet N. L.
Abstract : Seleniferous soil collected from the wheat ( Triticum aestivum L.)‐grown agricultural land in Punjab, India, was characterized and the Se concentration in various soil fractions was determined by sequential extraction. The soil had a total Se content of 4.75 (±0.02) mg kg −1, of which 44% was observed in the oxidizable soil fraction. Soil flushing as an in situ technique was performed to simulate the Se migration pattern in case of rainfall or irrigation. Significant migration of Se from the upper layer to the lower layers was observed during water percolation through the soil column at a flow rate of 1 mL min −1, which could be attributed to Se reduction in the lower anoxic layers of the soil column. For ex situ treatment, the soil washing technique was optimized by varying different parameters such as treatment time, temperature, pH, liquid to solid (L:S) ratio, and presence of competing ions and oxidizing agents. Selenium extraction from soil was significantly improved by the presence of oxidizing agents in the washing solution: ∼38% Se was removed from the soil in the presence of 0.5% KMnO4 . In contrast, parameters such as treatment time, temperature, pH, L:S ratio, and competing ions did not significantly enhance the Se extraction efficiency. In this research, laboratory‐scale in situ and ex situ treatment techniques for Se removal from soil were studied and optimized. The results provide an insight for large‐scale Se removal and recovery from seleniferous soils. Core Ideas: Total Se content in the seleniferous soil was 4.75 (±0.02) mg kg −1 . Around 44% Se is present in the oxidizable or "organically associated" fraction in soil. Selenium migrated to lower layers in the soil column during flushing. Maximum Se extraction was achieved with oxidizing agents compared with other parameters.